Exploring Sundanese Cultural Heritage: An Analysis of Wayang Golek Stories in the Islamization of West Java - Iryana, Wahyu; Sujati, Budi; Ningsih, Arum (Jurnal Adabiyah, 2025)
Wayang Golek is one of the Sundanese cultural forms derived from the Indian epics, the Mahabharata and Ramayana. The Sundanese Wayang Golek originated from the long process of Sunan Kalijaga's preaching journey, which spread Islam through culture. The Wayang Golek performance is told by puppeteers who provide entertainment, spectacle, and guidance for the community. The play that is very memorable and in demand by wayang fans is the Jamus Layang Kalimahsahda play, which is phenomenal. People who have the Jamus Layang Kalimahsahda will become invincible. This article presents a Critical review of the Teachings of Tauhidan Habluminallah, exploring the process of horizontal communication between humans and God, combined with cultural narratives. The methods used are literature review, observation, and interviews. The initial conclusion describes how the Sundanese wayang golek serves as a cultural ritual that guides society with the teachings of tauhid and the philosophy of life in the world. ملخص وايانغ جوليك هو شكل من أشكال الثقافة السوندية، متجذر في الملاحم الهندية، المهابهاراتا ورامايانا. نشأ وايانغ جوليك السوندية من مسيرة الدعوة الإسلامية الطويلة لسونان كاليجاغا، التي نشرت الإسلام عبر الثقافة. يؤدي عروض وايانغ جوليك محركو الدمى (الدالانغ)، الذين يقدمون الترفيه والعروض المسرحية والإرشاد للمجتمع. ومن المسرحيات التي لا تُنسى والمرغوبة بشكل خاص بين محبي وايانغ مسرحية "جاموس لايانغ كاليمهسدا" (القوة السحرية للكلمة السحرية). من يمتلك "جاموس لايانغ كاليمهسدا" يصبح لا يُقهر. تقدم هذه المقالة مراجعة نقدية لتعاليم "توحيد الله"، مستكشفةً عملية التواصل العمودي بين البشر والله، مقترنةً بالسرديات الثقافية. الأساليب المستخدمة هي مراجعة الأدبيات والملاحظة والمقابلات. يصف الاستنتاج الأولي كيف يعمل وايانغ جوليك السونداني كطقس ثقافي يُرشد المجتمع بتعاليم التوحيد وفلسفة الحياة في هذا العالم. Abstrak Wayang Golek merupakan salah satu bentuk budaya Sunda yang bersumber dari epos India, Mahabharata dan Ramayana. Wayang Golek Sunda berawal dari proses panjang dakwah Sunan Kalijaga yang menyebarkan agama Islam melalui budaya. Pertunjukan Wayang Golek dipentaskan oleh dalang yang memberikan hiburan, tontonan, dan tuntunan bagi masyarakat. Lakon yang sangat berkesan dan diminati oleh penggemar wayang adalah lakon Jamus Layang Kalimahsahda yang fenomenal. Orang yang memiliki Jamus Layang Kalimahsahda akan menjadi tak terkalahkan. Artikel ini menyajikan tinjauan kritis terhadap ajaran Tauhidan Habluminallah, mengeksplorasi proses komunikasi vertikal antara manusia dan Tuhan, dipadukan dengan narasi budaya. Metode yang digunakan adalah kajian pustaka, observasi, dan wawancara. Kesimpulan awal menggambarkan bagaimana wayang golek Sunda berfungsi sebagai ritual budaya yang membimbing masyarakat dengan ajaran tauhid dan falsafah hidup di dunia.